Enhancing the Value Care of Lung Cancer Treatment for Medically Underserved Population in Kentucky - Sari, Morita; Jr, James. W. Holsinger; Wackerbarth, Sarah; Ingram, Richard (Universitas Muhammadiyah Surakarta, 2016)
Background: For many years Kentucky has had the nation’s highest lung cancer incidence. Kentucky is one of the thirteen states in Appalachia in which the difference in wealth is a key determinant of health since residents of Appalachia do not have access to the same financial resources as the rest of the US population. In this study, the value of lung cancer treatment for a medically underserved population (Appalachia) would be evaluated based on health insurance type and treatment pattern. Methodology: Data for lung cancer cases diagnosed between 2000 and 2011 were obtained from the Kentucky Cancer Registry (KCR). The cohort included 49,512 patients who met the following inclusion criteria. Patients were classified into two distinct groups based on county location: Appalachian and Non-Appalachian. Chi-square, Cox survival regression analysis, and Kaplan Meier survival trend were performed to identify variables affecting treatment and survival. Result: The analysis evaluated 49,512 patients from KCR. For all population, sex (p<.0001), age group (p<.0001), Stage (p<.0001), insurance type (p<.0001) and county (p<.0001) were significantly associated with the type of treatment. Conclusions: Eventhough the strongest predictors for survival in lung cancer are age and cancer Stage, health insurance does have a significant impact on improving the survival rate. Overall, early diagnosis and timely follow up are imperative for improving the value care in lung cancer treatment